PHARMA 4.0–IMPACT OF THE INTERNET OF THINGS ON HEALTH CARE - A. T., PRAJWAL; B. S., MUDDUKRISHNA; VASANTHARAJU, S. G. (International Journal of Applied Pharmaceutics, 2020)
The IoT in health care is currently booming in the world of health care in particular. Industry has risen from generation 1.0 to 4.0 during the Internet of things period. As we remember, we came across the exact submission of the traditional health care system. Each time the patient has needed to visit the clinic/hospitals, even for small complications that may affect the patient's medical costs along with time and energy. One more significant factor is also an emergency; otherwise, she/he/older population was unable to demand urgent assistance from the older system of healthcare. And yet somehow, the situation has changed with the use of the cyber-physical world; we are heading out of the 4th phase of the health care industry means smart health care network. This paper offers an insight into different facets of how healthcare systems such as doctors, hospitals, and of course, patients are powered by the internet of things and how can it track and ensure fast, quality, and efficient use of less time also in a smart way. Here, a patient knows how to track patients by using a collection of different wearable sensor nodes for real-time monitoring and examination of specific patient criteria. One of the most boosting subjects characterizes the development of medical technology within their own homes, enabling older or physically weak people to stay as long as possible at home while being medically cared for and monitored. We searched literature and guidelines in Pubmed, Web of Science, Google Scholar, Scopus, CNKI, and Embase databases up to 2019. The following search terms alone or matched with the Boolean operators ‘AND’ or ‘OR’ were used: "Nanoparticles", “Anticancer treatment", ‘Bioflavonoids’, ‘Plant origin drugs’, ‘Nano formulations’, ‘Cancer’ and ‘Novel drug delivery systems’. We focused on full-text articles, but abstracts were considered if relevant.